ANALISIS BAURAN PEMASARAN TERHADAP PERILAKU KONSUMEN PRODUK PANGAN ORGANIK - Farida, Farida (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study was aimed to analyze the effect of marketing mix consist of product, price, place, promotion, and service on consumer satisfaction and repurchase intention of organic food products. Fifty-four respondent were selected by convenience sampling method to collect information from the respondent by filled the sheet questionnaires to obtain primary data. The data were analyzed by using multiple regression method. The result of the study showed that the marketing mix was influenced significantly on customer satisfaction by 99,7percent and 80,4 percent was affected by repurchase intention. Product was a variable of marketing mix had more important to influence customer satisfaction and repurchase intention for organic food products. Marketing mix product, price, place, promotion, and service partially have a significant effect on consumer satisfaction. Product, price, and service significantly affected on repurchase intention, whereas place and promotion was no significant effect. Key words: organic food, marketing mix, consumer satisfaction, repurchase intention